Gentle Birth Untuk Persalinan Nyaman Pada Kelas Ibu Hamil Di Polindes Desa Awang Bangkal - Rafidah, Rafidah; Isnaniah, Isnaniah; Rohmah, Nur; Januarsih, Januarsih; Megawati, Megawati (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
Childbirth is a natural process experienced by women as one of the life cycles, 90-95% of deliveries should be able to proceed normally vaginally without complications. Based on data from the 2017 Indonesian Demographic and Health Survey (IDHS), anxiety or severe pain in labor was 53.9%. When experiencing excessive anxiety, fear, and anxiety, the body will produce stress hormones in the form of adrenaline and increase pain in labor. It was this paradigm that gave birth to a calm and polite birth method that made use of all natural elements, which was called a gentle birth. Gentle birth is one way to prepare pregnant women during pregnancy. Giving birth with a gentle birth gives pregnant women a sense of security and confidence to use their own abilities and strengths to give birth to babies. The activity begins with a physical examination of pregnant women then provides health education about classes for pregnant women and the gentle birth method. The last activity is evaluation and question and answer about health education that has been given to pregnant women. Through this community service activity, it is hoped that it can increase the knowledge of pregnant women in villages that provide services at the Polindes so that pregnant women can face childbirth comfortably and with minimal trauma and pain.